LEGAL MECHANISMS OF FUNCTIONING OF THE AIFC ARBITRATION SYSTEM (Journal of actual problems of jurisprudence, 2024)
The International Arbitration Center (IAC) and the Astana International Financial Center (AIFC) Court together form the dispute resolution mechanism in the AIFC. The IAC was set up to provide an alternative to court litigation, which provides independent, fair and high-quality arbitration. Due to the particularity of AIFC in Kazakhstan's legal system, the dispute resolution mechanism of the AIFC has been paid more attention. To provide investors with efficient and friendly investment environment, it is necessary to study the AIFC dispute resolution mechanism under the existing legal framework. The purpose of the article is to identify the legal system of the functioning of the IAC arbitration as part of the AIFC dispute resolution mechanism and its effectiveness, which is achieved by analyzing the arbitration proceedings and the affecting factors. Based on the study, the AIFC dispute resolution mechanism made up by the IAC and the Court practices with the widely-accepted international principles and standards. It is a combination of the novelty of the practice of the AIFC scheme and Kazakhstan's domestic arbitration ground. Such research hopefully helps the investors to know about the AIFC dispute resolution mechanism, and tries to trigger further study to promote the development of the AIFC. Keywords: Kazakhstan, dispute resolution, arbitration, Astana International Financial Center, International Arbitration Center, the AIFC Court, arbitration procedure, legal system.